The Potential of Biogas from Organic Waste in the Talumelito Landfill as a Source of Renewable Energy - Harun, Ervan Hasan; Ilham, Zul; Ilham, Jumiati; Yusuf, Taufiq Ismail (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Environmental issues and the need for renewable energy sources have driven innovation in utilizing waste as a raw material for energy production. This study aims to assess the potential of organic waste from the Talumelito landfill in Gorontalo Regency as a source of electricity through biogas technology. The methods used involve a mixed approach, combining quantitative measurements of the amount of organic waste and qualitative analysis of the potential biogas and electricity that can be generated. The results show that in one week, a total of 587,427 kg of waste was disposed of at the Talumelito landfill, with 41,650 kg (7.1%) being organic waste. From this organic waste, an average daily biogas volume of 825.6 m³ was obtained, producing a weekly methane gas volume of 3,688.5 m³. The potential electricity generated from this organic waste is 34,634.9 kWh per week, or approximately 4,947.8 kWh per day. The study concludes that organic waste at the Talumelito landfill has significant potential to be developed as an environmentally friendly electricity source.Masalah lingkungan dan kebutuhan akan sumber energi baru terbarukan (EBT) yang ramah lingkungan mendorong inovasi dalam pemanfaatan sampah sebagai bahan baku energi. Penelitian ini bertujuan untuk mengkaji potensi pemanfaatan sampah organik dari Tempat Pembuangan Akhir (TPA) Talumelito di Kabupaten Gorontalo sebagai sumber energi listrik melalui teknologi biogas. Metode yang digunakan adalah pendekatan gabungan (mixed methods) yang melibatkan pengukuran kuantitatif terhadap jumlah timbulan sampah organik dan pendekatan kualitatif untuk menganalisis potensi biogas serta energi listrik yang dapat dihasilkan. Hasil penelitian menunjukkan bahwa dalam satu minggu, total sampah yang masuk ke TPA Talumelito adalah 587.427 kg, dengan jumlah sampah organik sebesar 41.650 kg (7,1%). Dari sampah organik ini, diperoleh volume biogas harian rata-rata sebesar 825,6 m³, dengan volume gas metana mingguan sebesar 3.688,5 m³. Potensi energi listrik yang dapat dihasilkan dari sampah organik tersebut adalah sebesar 34.634,9 kWh per minggu, atau sekitar 4.947,8 kWh per hari. Kesimpulan dari penelitian ini menunjukkan bahwa sampah organik di TPA Talumelito memiliki potensi signifikan untuk dikembangkan sebagai sumber energi listrik yang ramah lingkungan.